Citric Acid-Based Treatment for Refining Mineral Fractions Recovered from Processed MSW Incinerator Bottom Ash - I. B. G. Sumbranang Adhiwiguna; Xinqi Yu; Ragnar Warnecke; Rüdiger Deike (Applied Sciences)
This research examines the possibility of the washing process as a supplementary operation after extensive extended physical separation sequences for processed incinerator bottom ash (pr.IBA), which is the mineral fraction resulting from conventional separation operation of municipal solid waste (MSW) incinerator bottom ash (IBA) in Germany. Citric acid is employed as the only primary treatment agent in several variations of parameter combinations. It includes the type of solvent, washing duration, acid concentration, liquid-to-solid ratio, and introduction of external agitation (stirring and heating). The analysis results revealed that the concentration of copper, zinc, and manganese in the mineral phase of pr.IBA can be reduced by the citric acid washing process. The most significant change is observed in the zinc content, where a reduction of up to 50% is successfully achieved. In contrast, the silicon concentration is relatively unaffected during citric acid washing, but a concentration decrease is detected for calcium. The aluminum and iron contents in the studied fraction of pr.IBA are also soluble in citric acid solution, although the rates are expected to be exceptionally slow. In this instance, stirring and heating over a prolonged washing duration are necessary before a decrease in their concentration can eventually occur.